Efficacy of Intra-Articular Autologous Platelet Rich Plasma Application in Knee Osteoarthritis - Havva TALAY ÇALIŞ,; Serap TOMRUK SÜTBEYAZ,; Emel GÜLER,; Canan HALICI,; Hatice SAYAN,; Ali KOÇ,; Metin KONK,; Jülide Aksel YAZICIOĞLU, (Archives of Rheumatology, 2015)
Objectives: This study aims to evaluate the efficacy of autologous platelet rich plasma applications on pain, functional status, and cartilage regeneration in advanced knee osteoarthritis. Patients and methods: A total of 82 patients (13 males, 69 females; mean age 63.5±9.3 years; range 40 to 88 years) with chronic knee pain for the last one year, who had grade 3-4 knee osteoarthritis according to Kellgren-Lawrence Scale and visual analog scale value of higher than 5, who did not receive physical therapy for the last six months, and did not respond to treatment despite use of nonsteroidal antiinflammatory drugs and analgesics at least for the last three months were enrolled in the study. Totally 103 knee joints of 82 patients were applied intra-articular platelet rich plasma in the beginning, and first and second weeks of treatment. Platelet rich plasma was applied to both knees in 20 patients. Patients were evaluated clinically with visual analog scale, functionally with Western Ontario and McMaster Universities Osteoarthritis Index, and six-minute walk test before application and after application at first and second weeks, and third and sixth months. Cartilage thicknesses were measured by ultrasound before treatment and at third and sixth months after treatment. Obtained results were compared. Results: Compared to values before treatment, patients’ visual analog scale values were significantly decreased at third and sixth months after treatment (p<0.001). When compared according to Western Ontario and McMaster Universities Osteoarthritis Index, all values improved significantly after treatment (p<0.001). Results of six-minute walk test improved at third and sixth moths after treatment compared to results before treatment (p<0.05). Cartilage thicknesses increased significantly after treatment at third and sixth months compared to before treatment (p<0.05). Conclusion: We believe that platelet rich plasma treatment is an effective, reliable, easily applied and low cost application in terms of pain, functional status as well as cartilage regeneration even in patients with advanced osteoarthritis.